Acute urinary retention and gastroparesis due to self-medication in an elderly male - Gumashta, Jyotsna; Gumashta, Raghvendra (International Journal of Research in Medical Sciences, 2020)
An eighty-five years old man complained of difficulty in swallowing for relatively dry food items and water with occasional episodes of vomiting. He was a diabetic and hypertensive patient on treatment for long, suddenly reported pain and discomfort in the abdomen with inability to pass urine. All the parameters were within normal limits except prostate being 70 ml enlarged. He was catheterized with diagnosis of BPH with chronic urinary retention. TURP was advised but the case did not consent for it. On close scrutiny of detailed history, it was observed that the patient was on self-medication of homeopathic drugs which were causing smooth muscle relaxation of bladder and GIT, causing difficulty in deglutition and constipation. On discontinuation of drugs, these effects disappeared and the case did not need any further catheterization, concluding that the acute urinary retention was caused by self-medication induced constipation. It is hence inferred that self-medication with homeopathic medicines should be avoided specially by elderly as aging effects and co-morbid condition often coexist.